Cement Grout Nonlinear Flow Behavior through the Rough-Walled Fractures: An Experimental Study. (4th January 2020) - Jin, Yuhao; Han, Lijun; Xu, Changyu; Meng, Qingbin; Liu, Zhenjun; Zong, Yijiang
Abstract : This research experimentally studied the effects of various fracture roughness (characterized by the fractal dimension D ) and normal stress (normal loads F N ) applied to fracture on ultrafine cement grout nonlinear flow behavior through rough-walled plexiglass fractured sample. A high-precision and effective sealing self-made apparatus was developed to perform the stress-dependent grout flow tests on the plexiglass sample containing rough-walled fracture (fracture apertures of arbitrary variation were created by high-strength springs and normal loads according to design requirements). The real-time data acquisition equipment and high-precision self-made electronic balance were developed to collect the real-time grouting pressure P and volumetric flow rate Q, respectively. At each D, the grouting pressure P ranged from 0 to 0.9 MPa, and the normal loads F N varied from 1124.3 to 1467.8 N. The experimental results show that (i) the Forchheimer equation was fitted very well to the results of grout nonlinear flow through rough-walled fractures. Besides, both nonlinear coefficient (a ) and linear coefficient (b ) in Forchheimer's equation increased with increase of D and F N, and the larger the F N was, the larger the amplitude was. (ii) For normalized transmissivity, with the increase of Re, the decline of the  T / T 0 − β curves mainly went through three stages: viscous regime, weak inertia regime, and finally strong inertia regime. For a certain D, as the normal load F N increased, the T / T 0 − β curves generally shifted downward, which shows good agreement with the single-phase flow test results conducted by Zimmerman. Moreover, with the increase of D, the Forchheimer coefficient β decreased. However, within smaller F N, β decreased gradually with increasing D and eventually approached constant values. (iii) At a given F N, J c increased with increasing D .